A' = A'B + A'B' and
B = BA' + BA
Now
A'D + BD + B'C + AB'D =
(A' + B + AB')D + B'C =
(A'B + A'B' + A'B + AB + AB')D + B'C =
(1)D + B'C
The 1st question is solved by 2 gentlemenProve i. AD + BD + BC + ABD = BC + D
ii. (x'y' + z)' + z + xy + wz = x + y + z
I'm new to Boolean algebra and I've tried all the rules for Boolean algebra without success. Help anyone?
Thread starter | Similar threads | Forum | Replies | Date |
---|---|---|---|---|
P | Boolean Algebra problem , need help | Homework Help | 9 | |
L | Help With Boolean Algebra | Homework Help | 3 | |
N | boolean algebra help. | Homework Help | 11 | |
D | boolean algebra help | Homework Help | 3 | |
R | Help needed with Boolean Algebra and DeMorgan | Homework Help | 9 |
by Jake Hertz
by Steve Arar